Metabolic Inhibitors as Stimulating Factors for Citric Acid Production (Biological Sciences - PJSIR, 2008)
The effect of some metabolic inhibitors on citric acid (CA) production by Aspergillus niger in cane molasses medium was investigated. Addition of 0.01-0.1 mM iodoacetic acid and sodium arsenate, 0.05-1.0 mM sodium malonate,0.01 mM sodium azide, 0.01-0.05 mM sodium fluoride, 0.1-1.0 mM EDTA stimulated CA production (5-49%). Higher concentrations (10 mM) of iodoacetic acid, sodium malonate and 0.5 mM sodium azide caused a complete inhibition of fungal growth. Iodoacetic acid, sodium arsenate and sodium fluoride (0.2 mM) caused a remarkable inhibition of CA production. The implications of those preliminary functions was discussed.